2015
DOI: 10.1177/0956797615590992
|View full text |Cite
|
Sign up to set email alerts
|

Facial Trustworthiness Predicts Extreme Criminal-Sentencing Outcomes

Abstract: Untrustworthy faces incur negative judgments across numerous domains. Existing work in this area has focused on situations in which the target's trustworthiness is relevant to the judgment (e.g., criminal verdicts and economic games). Yet in the present studies, we found that people also overgeneralized trustworthiness in criminal-sentencing decisions when trustworthiness should not be judicially relevant, and they did so even for the most extreme sentencing decision: condemning someone to death. In Study 1, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
247
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(276 citation statements)
references
References 30 publications
14
247
1
3
Order By: Relevance
“…Criminal appearance has been found to affect decisions related to the criminal justice system (see for instance Flowe & Humphries, 2011;Funk & Todorov, 2013). For researchers, our findings present two tools to create faces that systematically vary along the perceived criminality dimension in order to advance our knowledge on the effect of appearance on legal outcomes (see for instance recent findings by Wilson & Rule, 2015, on the link between untrustworthy appearance and extreme sentencing outcomes).…”
Section: Discussionmentioning
confidence: 90%
“…Criminal appearance has been found to affect decisions related to the criminal justice system (see for instance Flowe & Humphries, 2011;Funk & Todorov, 2013). For researchers, our findings present two tools to create faces that systematically vary along the perceived criminality dimension in order to advance our knowledge on the effect of appearance on legal outcomes (see for instance recent findings by Wilson & Rule, 2015, on the link between untrustworthy appearance and extreme sentencing outcomes).…”
Section: Discussionmentioning
confidence: 90%
“…People dehumanize convicts (Bastian, Denson, & Haslam, 2013), finding it easier to punish those for whom they engage in less configural processing (Fincher & Tetlock, 2016). Trustworthiness predicts the harshness of sentencing (Wilson & Rule, 2015, 2016). Because Black versus White convicts are more dehumanized even if their crimes are similar (Goff et al, 2008), it suggests that the interface between configural face processing and reduced trust may affect how people of different races are sentenced.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Sofer, Dotsch, Wigboldus, and Todorov (2015) examined the linkage between facial typicality and facial attractiveness on the perceived trustworthiness of the person being pictured. As another example, Wilson and Rule (2015) showed that judgments about how trustworthy criminals' faces looked predicted sentencing decisions, even in the presence of more seemingly relevant data (see also Wilson & Rule, 2016). Applying such findings to a protégé forming trust in a potential mentor, the results suggest that the protégé might be influenced by how typical the mentor's face looks, or how attractive it seems.…”
Section: Study 1: Theory Developmentmentioning
confidence: 92%